Assessment of particle packing characteristics at interfaces by space system - Stroeven, Piet (Image analysis and stereology, 2000)
Interest in material structure has been raised by upgrading of cementitious systems. Computer-simulation of material structure has been pursued so far by using random generators. Such systems were successfully applied for estimatingglobal properties. Realistic estimation of structure-sensitive properties, however requires a more appropriate simulation of material structure. The SPACE (Software Package for the Assessment of Compositional Evolution) system has been developed for that purpose. It incorporates particle interaction and gravitational influences, which are typical for the `natural' processes underlying the formation of material structure in the production stage. The capabilities are discussed of the two computersimulationmethods for generating structural information relevant for either structure-insensitive, or structure-sensitive properties in bulk and inthe interfacial transition zone (ITZ). The structural information will deal with composition and configuration of the material, respectively. The use of random generatorbased (RG) systems is demonstrated not justified when dealing with structure-sensitive problems.
Keywords: Delec, velikost; Materials Testing; Particle Size; Materiali, testiranje; Computer Simulation; Računalniška simulacija; Slika, obdelava z računalnikom; Image Processing, Computer-Assisted; preikava materiala; obdelava slik